Morse-Bott approach to monopole Floer homology and the Triangulation conjecture - Lin, Francesco (Memoirs of the American Mathematical Society ;, 2018)
"In the present work we generalize the construction of monopole Floer homology due to Kronheimer and Mrowka to the case of a gradient flow with Morse-Bott singularities. Focusing then on the special case of a three-manifold equipped equipped with a spin[superscript]c structure which is isomorphic to its conjugate, we define the counterpart in this context of Manolescu's recent Pin(2)-equivariant Seiberg-Witten-Floer homology. In particular, we provide an alternative approach to his disproof of the celebrated Triangulation conjecture."--Pgae v